2016
DOI: 10.1080/02770903.2016.1180530
|View full text |Cite
|
Sign up to set email alerts
|

Berberine improves airway inflammation and inhibits NF-κB signaling pathway in an ovalbumin-induced rat model of asthma

Abstract: The findings suggested a therapeutic potential of berberine on OVA- induced airway inflammation. The ameliorative effects on the OVA-induced airway inflammation might be associated with the inhibition of the NF-κB signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 47 publications
1
28
1
Order By: Relevance
“…Several pharmaceutical tactics, such as formulation with permeability enhancers, P-gp inhibitors, muco-adhesive agents have been attempted to eradicate pharmaceutical incompetence of berberine; however, application of nanotechnology has been found to be the most promising tool to improve oral bioavailability and therapeutic efficacy of berberine [249]. Dendrimers-encapsulated berberine, berberine-assembled polymer-lipid hybrid nanoparticles, and chitosan-coated nanoliposomes of berberine have been reported to facilitate oral delivery of berberine with improved pharmaceutical attributes [250][251][252].…”
Section: Berberinementioning
confidence: 99%
“…Several pharmaceutical tactics, such as formulation with permeability enhancers, P-gp inhibitors, muco-adhesive agents have been attempted to eradicate pharmaceutical incompetence of berberine; however, application of nanotechnology has been found to be the most promising tool to improve oral bioavailability and therapeutic efficacy of berberine [249]. Dendrimers-encapsulated berberine, berberine-assembled polymer-lipid hybrid nanoparticles, and chitosan-coated nanoliposomes of berberine have been reported to facilitate oral delivery of berberine with improved pharmaceutical attributes [250][251][252].…”
Section: Berberinementioning
confidence: 99%
“…While, berberine, baicalin, baicalein, wogonoside, wogonin and geniposide have been identified, and been considered as the main bioactive components in HLJDD [27, 29]. In those identified components, berberine and baicalin have been reported to possess anti-inflammatory effects and have been used to treat many diseases [30]. Ni et al reported that the berberine exhibited a strong renoprotective effects in in vivo diabetic nephropathy model [31].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, berberine, pyrogallol, catechin dimers, and resveratrol 3-O-β-glucoside have shown anti-inflammatory effects in various studies. Berberine was observed to inhibit the production of proinflammatory cytokines interleukin (IL)-6 and chemokines IL8 in HaCaT stimulated with sulfur mustard (Lang et al, 2018 ) and their anti-inflammatory effects have been linked to the inhibition of the nuclear factor-κB (NF-κB) signaling pathway (Li et al, 2016 ). Catechin dimers (Andre et al, 2012 ) and resveratrol 3-O-β-glucoside (Potapovich et al, 2011 ) have also been shown to inhibit NF-κB activation in TNF- α-stimulated-NF-κB/SEAP (Secreted alkaline phosphatase) HEK 293 cell lines and TNF-α-plus-IFN-γ-stimulated primary human keratinocytes.…”
Section: Resultsmentioning
confidence: 99%